Obtenção e sinterização de nanopartículas de ZrO2-4,5%Y2O3 - Grzebielucka, Edson Cezar (2009)
The powders synthesis of yttria-stabilized zirconia by chemical methods has enabled the reduction in particle size for the submicrometer-sized scale. This reduction is to improve the electrical and mechanical responses of electrolyte fuel cells. Contributing in this research, this work was to study the effects of temperature elimination of organic phases, to obtain powder of yttria stabilized zirconia, and the effect of time and sintering temperature on grain size of sintered bodies. The powders were obtained by two chemical routes: Pechini and PEG / AF, using 4.5 mol% of Y2O3 as a dopant. The properties of powders were made by X-ray Diffraction, Scanning Electron Microscopy and Infrared Spectroscopy and the sintered bodies were characterized by X-ray diffraction, scanning electron microscopy and density. It was observed that the coordination of metal ions with the polymer occurs through different ways, depending on the process used to obtain the post. The final microstructure has a greater influence than the sintering of treatments for removal of organics. The method of production of powders, temperature and calcination time change the size of the crystallites formed, and the largest variation in size occurs when increasing the calcination temperature. The final size of the grains obtained after sintering was about 1μm not influenced by the method or by the firing conditions for obtaining the post. Crystallite size obtained by Scherrer equation reported values between 5 and 8nm, and that the crystallite size tends to increase with time and temperature of heat treatment.